(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
Economic analysis of the Natural resources gives information about nature values of the existing territory what is a precondition for e successful farther development of territory. Society pays attention to restrictedness problem of natural resources more and more; in the whole world scientists searches for different solutions, how to combine our wills and provide reserves of natural resources for next generations.In our article we have analysed one of the most important natural resources (Forests and agricultural used land) economically, whose reasonable use provides a successful development of economy in the region.The fallowing research methods were used: abstractly logical, graphical, monographic, document analysis, deduction, synthesis and statistical methods.